2018
DOI: 10.3892/ol.2018.9188
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy for centrally‑located lung tumors with 56�Gy in seven fractions: A retrospective study

Abstract: Stereotactic body radiotherapy (SBRT) for centrally-located lung tumors remains a challenge because of the increased risk of treatment-related adverse events (AEs), and uncertainty around prescribing the optimal dose. The present study reported the results of central tumor SBRT with 56 Gy in 7 fractions (fr) at the University of Tokyo Hospital. A total of 35 cases that underwent SBRT with or without volumetric-modulated arc therapy consisting of 56 Gy/7 fr for central lung lesions between 2010 and 2016 at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 51 publications
0
17
3
Order By: Relevance
“…Two reports with three and four ultra-central patients, respectively, were also excluded due to small sample sizes, with one reporting no toxicity (0 of 3 patients) and the other not directly reporting the toxicity rate for patients considered ultra-central. 32,33 We believe that our results will shed light on the feasibility of SABR for ultra-central lung lesions, as well as provide guidance on patient selection so that those patients at higher risk are adequately counselled on the competing risks and benefits of SABR. 34 Ultimately, further prospective research in this setting is needed to define the optimal dose and fractionation of radiation for ultra-central tumors, and the results of one such study (SUNSET: SABR for Ultra-central NSCLC: A Safety and Efficacy Trial, NCT03306680) are awaited.…”
Section: Discussionmentioning
confidence: 85%
“…Two reports with three and four ultra-central patients, respectively, were also excluded due to small sample sizes, with one reporting no toxicity (0 of 3 patients) and the other not directly reporting the toxicity rate for patients considered ultra-central. 32,33 We believe that our results will shed light on the feasibility of SABR for ultra-central lung lesions, as well as provide guidance on patient selection so that those patients at higher risk are adequately counselled on the competing risks and benefits of SABR. 34 Ultimately, further prospective research in this setting is needed to define the optimal dose and fractionation of radiation for ultra-central tumors, and the results of one such study (SUNSET: SABR for Ultra-central NSCLC: A Safety and Efficacy Trial, NCT03306680) are awaited.…”
Section: Discussionmentioning
confidence: 85%
“…There was no significant difference in treatment outcome between the two methods (41). VMAT plans were designed using a single partial arc with angle ranges of -40˚ to 180˚ (left lung) or -180˚ to 40˚ (right lung), as previously detailed (37,38,41,42). dosimetric planning and plan analysis were performed using Pinnacle 3 .…”
Section: Methodsmentioning
confidence: 99%
“…dosimetric planning and plan analysis were performed using Pinnacle 3 . The collapsed cone convolution method (comparable to the superposition method) in the TPS was used (42,43). All final calculations were performed using a grid size of 2.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Data on treating central thoracic metastases with SBRT is limited, as the delivery of SBRT within the NFZ has been controversial since an early study in NSCLC demonstrated severe toxicity and high rates of treatment-related death [4]. Although several retrospective studies have now demonstrated that moderately central primary and metastatic tumours can be treated safely using moderated dose fractionations [5,6,[8][9][10]18], other studies report high toxicity rates [19,20]. The evidence for ultra-central tumours is more equivocal.…”
Section: Discussionmentioning
confidence: 99%